Віддалені результати застосування автотрансплантації тканини щитоподібної залози з метою профілактики поопераційного гіпотиреозу - Черенько, С. М.; Ларін, О. С.; Підаєв, А. В.; Товкай, О. А.; Січінава, Р. М. (Clinical Endocrinology and Endocrine Surgery, 2013)
The paper analyzed the data of long follow-up results of 46 from total group of 57 patients to whom autotransplantation of cryopreserved thyroid tissue to the anterior abdominal muscle since 3-7 days after thyroidectomy. The share of patients to whom replacement thyroxine therapy was unnecessary shortened from 54 % to 13 %. Partly dependent on thyroxine therapy patients comprised 67 % (from 37 % at the beginning of observation). Low efficacy of autotransplantation was observed for 9 % during the 1-st year and 20 % after 5-7 years of operation.